The Complexity of Fulfilling the Rights of Persons with Disabilities in the Implementation of Elections: A Literature Study - Muhammad Risal Arifin (Westscience Press, 2023)
General elections are a form of channeling people's sovereignty to produce a democratic government. Every democratic country wants to create inclusive elections. In the implementation of elections, the participation of the entire community is one of the main factors in the success of inclusive elections. Therefore, the participation of persons with disabilities as vulnerable groups in the implementation of elections is a crucial issue that needs attention. The limitations that persons with disabilities have often result in problems in fulfilling their rights in the implementation of elections. Therefore, regulations are needed so that the distribution of the rights of persons with disabilities in elections can be realized. This research uses a literature approach. This research aims to present the complexity of persons with disabilities in the implementation of elections so that it is expected to contribute to the benchmark for inclusive elections.